2014
DOI: 10.1614/ws-d-13-00091.1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Triggers of Winter Annual Weed Emergence in the Midwestern United States

Abstract: Winter annual weeds are becoming prolific in agricultural fields in the midwestern United States. The objectives of this research were to understand the roles of soil temperature (daily average and fluctuation) and moisture on the emergence of nine winter annual weed species and dandelion and to develop predictive models for weed emergence based on the accumulation of modified thermal/hydrothermal time (mHTT). Experiments were established at Lincoln, NE; Mead, NE; and at two sites (irrigated and rainfed) near … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 33 publications
1
29
0
3
Order By: Relevance
“…Yet, several plants of the spring cohort did not vernalize and produce any seeds. Andersson et al (2002) showed that downy brome emergence was delayed in no-till; in our study, spring emergence of downy brome began in May, 2 to 3 weeks later than it occurs in tilled systems (Werle et al 2014). Finnerty and Klingman (1962) found that downy brome vernalization was greater with short day lengths.…”
Section: Underseeding Annual Clovers In Winter Wheatsupporting
confidence: 45%
“…Yet, several plants of the spring cohort did not vernalize and produce any seeds. Andersson et al (2002) showed that downy brome emergence was delayed in no-till; in our study, spring emergence of downy brome began in May, 2 to 3 weeks later than it occurs in tilled systems (Werle et al 2014). Finnerty and Klingman (1962) found that downy brome vernalization was greater with short day lengths.…”
Section: Underseeding Annual Clovers In Winter Wheatsupporting
confidence: 45%
“…(turnip), Bidens pilosa (beggarticks), Ipomoea grandifolia (bindweed), Sida rhombifolia (arrowleaf sida), Richardia brasiliensis (tropical Mexican clover) and Amaranthus viridis (large fruit amaranth) for the three sowing seasons. Weed populations in agricultural crops usually consist of a hierarchy of individuals with one or two dominant species and others of less importance (Werle et al, 2014a).…”
Section: Resultsmentioning
confidence: 99%
“…Os dados de emergência são convertidos de contagens semanais para emergência cumulativa, com base na emergência total de mudas (Masin et al, 2012;Werle et al, 2014aWerle et al, , 2014b. Da mesma forma, os dados de temperatura e umidade são utilizados para determinar o TT ou TH, de acordo com equação sugerida por Gummerson (1986):…”
Section: Procedimento Da Modelagem Utilizando O Tempo Hidrotérmicounclassified
“…O conhecimento dos sistemas biológicos onde estas tecnologias são empregadas torna-se fundamental para a implementação de estratégias de manejo (Werle et al, 2014b) e aprimoramento de tecnologias.…”
Section: Introductionunclassified